Imaging electron flow from collimating contacts in graphene. (22nd March 2018) - Bhandari, S; Lee, G H; Watanabe, K; Taniguchi, T; Kim, P; Westervelt, R M
Abstract: The ballistic motion of electrons in graphene opens exciting opportunities for electron-optic devices based on collimated electron beams. We form a collimating contact in a hBN-encapsulated graphene hall bar by adding zigzag contacts on either side of an electron emitter that absorb stray electrons; collimation can be turned off by floating the zig-zag contacts. The electron beam is imaged using a liquid-He cooled scanning gate microscope (SGM). The tip deflects electrons as they pass from the collimating contact to a receiving contact on the opposite side of the channel, and an image of electron flow can be made by displaying the change in transmission as the tip is raster scanned across the sample. The angular half width Δ θ of the electron beam is found by applying a perpendicular magnetic field B that bends electron paths into cyclotron orbits. The images reveal that the electron flow from the collimating contact drops quickly at B   =  0.05 T when the electron orbits miss the receiving contact. The flow for the non-collimating case persists longer, up to B   =  0.19 T, due to the broader range of entry angles. Ray-tracing simulations agree well with the experimental images. By fitting the fields B at which the magnitude of electron flow drops in the experimental SGM images, we find Δ θ   =  9° for electron flow from the collimating contact, compared with Δ θ   =  54° for the non-collimating case.